The mediating role of self-esteem in the relationship between family functioning and symptoms of eating disorder in adolescents during home quarantine duo to coronavirus (COVID-19) - Gholami hosnaroudi, Motahareh; Kachooei, Mohsen; Fatehi, Nazanin (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the mediating role of self-esteem in the relationship between family functioning and symptoms of eating disorder in adolescents during home quarantine duo to COVID-19. Methods: The research method was descriptive-correlational, and the statistical population consisted of all students aged 13 to 18 years in Tehran in the academic year of 2019-2020. Among them, 384 individuals were selected by convenient sampling method. Family functioning Questionnaire (Faces-III) by Olson (1986), Eating Disorders Diagnostic Scale (EDDS) by stice et al (2000), and self-esteem scale (RSES) by Rosenberg (1965) were used to measure the variables. Data were analyzed through mediation analysis using AMOS software. Results: The results of the mediation analysis showed that the direct effect of family functioning on symptoms of eating disorder was significant (p<0/01; β -= 0/317). The indirect effect of family functioning on symptoms of eating disorder through self-esteem was also significant (p<0/05; β = -0/056). Conclusion: The present study has provided some evidence regarding the importance of the family psychological atmosphere in the occurrence and exacerbation of the adolescents’ symptoms of eating disorder during quarantine due to COVID-19. These results can provide a framework for developing novel prevention and therapeutic programs at different levels of eating disorder.